Rhyme in Shakespeare's theatre - Clark, M (2022)
This thesis analyses, contextualises, and celebrates rhyme in Shakespeare’s plays. Taking a historical formalist methodology, it reads rhyme’s local and structural functions both in aesthetic terms and within the network of cultural, textual, and theatrical associations that nourish them. The audiences’ varied horizons of expectation regarding rhyme – from literary reading, earlier forms of theatre, previous encounters with Shakespeare and other early modern dramatists, and wider performance culture – provide a basis for examining rhyme’s effects and allusions. The thesis explores the fully rhyming drama that preceded and influenced Shakespeare’s theatre; the productive tension in early modern dramatic rhyme between the classical and the English; the self-reflexive humour of Shakespeare’s early comedies; the different ways in which two Henriads invoke the register of the Mirror for Magistrates; the development of the rhyming lover; the influence of clowns, fools, and their improvised rhyme performances on Shakespeare’s work, specifically King Lear; the ways in which Othello, Hamlet, and Macbeth subvert different established conventions of the early modern dramatic couplet; Shakespeare’s negotiation of the line and the line ending in his late work, and its relation to the human and the wild in Cymbeline; and finally the legacy of Shakespearean dramatic rhyme, with brief discussions of post-Restoration adaptations and contemporary hip-hop Shakespeare productions. The thesis aims to be holistic not only in its approach to the various agents of theatre experience, but also in the way it views rhyme within a play. Rather than focusing solely on specific instances in their local contexts, it considers these moments as parts of broader structural and tonal principles. The argument of this thesis is that Shakespeare’s dramatic rhyme is worthy of study, not only for its powerful place in individual moments, but as a device with far-reaching associations and engagements: structural, allusive, and cultural.